The RISE ME Clinical Supervision Model Based on Microsoft Teams to Enhance Teacher Performance - Stefanus Lahade; Yari Dwikurnaningsih; Marinus Waruwu (Universitas Pendidikan Ganesha, 2023)
The development of the RISE ME clinical supervision model using the Microsoft Teams application is a model that integrates the Microsoft Teams application into the implementation of clinical supervision. This research aims to analyze the current implementation of clinical supervision, develop the model, and analyze the model's effectiveness on teacher performance. The research utilizes the Research and Development method. Data collection is done through interviews, questionnaires, and documentation. Data analysis is conducted descriptively and qualitatively. In this study, several challenges were found in the current implementation of clinical supervision by school principals, including low teacher initiative to request clinical supervision and a lack of flexibility in the implementation of clinical supervision. Based on the preliminary research, a technology-based clinical supervision model was developed and validated by experts, becoming a valid model. Furthermore, the model was tested on a limited scale, effectively improving teacher performance. The current clinical supervision model is still not effective. The needed clinical supervision model at present is technology-based. The developed model effectively improves teacher performance.